Implementasi Good Corporate Governance (GCG) Terhadap Nilai Perusahaan - Dewi Sekar Tanjung; Setiawati, Erma (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to identify the influence of managerial ownership, institutional ownership, independent board of commissioners, and audit committee on firm value in the manufacturing sector listed on the Indonesia Stock Exchange during the period 2019-2023. The method used is quantitative with an associative approach and multiple linear regression analysis. The research population consists of manufacturing companies listed during the period, with a sample selected using purposive sampling. The results show that managerial ownership does not affect firm value, while institutional ownership has a significant influence. The independent board of commissioners and audit committee did not show significant effects on firm value. This study has limitations in terms of the sample being limited to the manufacturing sector and only analyzing the aspect of Good Corporate Governance (GCG) without considering other factors that could influence firm value. Recommendations for future research include expanding the sample, considering additional variables, and using more complex econometric approaches.